An Analysis of Execution of Employee Compensation In Indonesia Post Company - Febiola, Mawar; Melandari, Nia; Farhan, Farhan; Ramadhan, Nazmi (Economics and Digital Business Journal, 2025)
This study is to find out the form of compensation and to find out more about the purpose of providing compensation to employees of PT Pos Indonesia Sentosa Raya Branch and to find out the obstacles that occur in the company in providing compensation to employees. The report on the results of the PBL compensation with the title "Employee Compensation System at PT Pos Indonesia Sentosa Raya Branch". The method used in this practice is the interview method. By obtaining data directly, such as making observations. The types of compensation available at PT Pos Indonesia Sentosa Raya Branch are in the form of salary, allowances, leave, and protection programs. The compensation system used by PT Pos Indonesia Sentosa Raya Branch is to use a time system to provide basic salary and other allowances